2009
DOI: 10.1590/s0037-86822009000300023
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa de Rickettsia spp em carrapatos Amblyomma cajennense e Amblyomma dubitatum no Estado de São Paulo

Abstract: A febre maculosa brasileira (FMB), doença causada pela bactéria Rickettsia rickettsii, é o principal agravo em conseqüência da infecção por riquétsias do grupo da febre maculosa (GFM) em humanos no Brasil. Casos confirmados de FMB têm sido relatados em determinadas áreas dos Estados da região Sudeste 18 . O carrapato Amblyomma cajennense é incriminado como o principal vetor da doença 5 e, embora não haja comprovação do papel do Amblyomma dubitatum na transmissão da FMB, suspeita-se de sua possível participação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 16 publications
6
32
0
11
Order By: Relevance
“…Although this result was in accordance with Guedes et al (2005), who also found no rickettsial infection in A. dubitatum from the same area of this study, it contrasts with other studies, especially in the state of São Paulo, where the majority of the A. dubitatum populations are infected with R. bellii (HORTA et al, 2007;PACHECO et al 2009). …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Although this result was in accordance with Guedes et al (2005), who also found no rickettsial infection in A. dubitatum from the same area of this study, it contrasts with other studies, especially in the state of São Paulo, where the majority of the A. dubitatum populations are infected with R. bellii (HORTA et al, 2007;PACHECO et al 2009). …”
Section: Discussionsupporting
confidence: 77%
“…Since we detected this rickettsial strain in nymphal pools, we suppose that the agent was infecting nymphs of one of the two Amblyomma species found at the study site, namely A. cajennense or A. dubitatum. Interestingly, this new rickettsial strain has never been reported before, even though hundreds of A. cajennense or A. dubitatum ticks have been tested for rickettsial infection in other areas (GUEDES et al 2005;SANGIONI et al, 2005;HORTA et al, 2007;PACHECO et al, 2009). Currently, R. tamurae is known to occur in Japan, where it infects the tick Amblyomma testudinarium (FOURNIER et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible that constant gene (and pathogen) exchange exists between ticks in the six sampled areas. Nonetheless, the present study corroborates a number of previous studies that have reported the presence of capybaras associated with the ticks A. cajennense and A. dubitatum in southeastern Brazil, in both BSF-endemic and non-endemic areas (GUEDES et al, 2005;PEREZ et al, 2008;TOLEDO et al, 2008;PACHECO et al, 2009;QUEIROGAS et al, 2012). The seasonal dynamics of A. cajennense has been well studied in southeastern Brazil, where this tick completes one generation per year, with larvae predominating in autumn, nymphs in winter and adults during spring and summer (OLIVEIRA et al, 2000(OLIVEIRA et al, , 2003LABRUNA et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Rickettsia bellii has been found in several tick species in the country, attaining high prevalence in both I. loricatus and A. dubitatum ticks, which may explain our serological results [6,10,27,32,37]. Reasons for the other probable homologous reactions, however, are less straightforward and deserve further investigation, particularly in the case of R. rickettsii.…”
Section: Discussionmentioning
confidence: 77%